PENGARUH PENGGUNAAN VIRTUAL PHYSICS LABORATORY TERHADAP PENGUASAAN KONSEP DAN KETERAMPILAN PROSES SAINS DI KELAS XII SMA - Eka Ratnasari (Physics and Science Education Journal (PSEJ), 2023)
This study aims to determine the effect of the Virtual Physics Laboratory (ViPhyLab) on the mastery of the concepts and skills of physics science processes at SMA N 4 Tanjung Jabung Barat. Students' mastery of concepts at SMA N 4 Tanjung Jabung Barat is still low, indicating low science process skills. This is due to the not optimal use of ICT-based learning media and inadequate facilities and infrastructure. This type of Â research isÂ  quasy experiment with this research sample using total sampling consisting of 2 classes as the experimental class and the control class. The instruments used in this study were multiple choice questions to measure mastery of concepts and essay questions and non-tests (observation sheets) to measure science process skills. The correlation coefficient value for concept mastery and science process skills is 0.993, a very strong category with a significant (2-tailed) < 0.001. The MANOVA test results obtained a significant level of 0.000 a (0.05). So that Ho is rejected and H1 is accepted. So it can be concluded that there is a significant influence of the Virtual Physics Laboratory learning media on the mastery of concepts and science process skills in class XII IPA 1 SMA N 4 Tanjung Jabung Barat.